AKIBAT HUKUM KRIMINALISASI PENGURUS SERIKAT PEKERJA ATAS TINDAK PIDANA PENCEMARAN NAMA BAIK TERHADAP KEDUDUKAN SERIKAT PEKERJA DI DALAM PERUSAHAAN (STUDI PUTUSAN PENGADILAN TINGGI DKI JAKARTA NOMOR: 95/PID/2018/PT.DKI) - Jefahnia Octaviani; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2019)
One of the legal subjects in the employment sector is labor unions. Labor unions are considered as organizations that able to help workers fight for their rights. When there is an industrial relations dispute between employers and workers, labor unions can represent their members in the process of resolutions that includes three steps, which are Bipartite, Tripartite, and Court of Industrial Relations. Based on the applicable laws, in order to carry out their main duties and functions, labor unions must be independent and democratic. Referring to DKI Jakarta High Court Judgement No. 95/Pid/2018/PT.DKI, two of labor union officials in PT Damira are prosecuted by third party outside of Bipartite for criminal acts of defamation, and the prosecution itself build upon their statements on Bipartite. This kind of prosecution can be categorized as a form of criminalization of labor union officials, thus raises issues of how legal protections for labor union officials who are prosecuted by third party and the impact of the criminalization of labor unions officials to the standing of labor unions. The author analyzes both issues comprehensively using the normative legal research method. According to the research, can be councluded that the legal protections of labor union officials is not carried out as stipulated in the applicable laws. Furthermore, criminalization of labor union officials has important impact which includes two things, namely the legal uncertainty of labor union officials regarding their status as workers and the standing of labor unions within the company after the criminalization.